Risk Assessment of Surface Water Contamination by Herbicide Residues: Monitoring of Propanil Degradation in Irrigated Rice Field Waters using HPLC-UV and Confirmation by GC-MS - Primel, Ednei Gilberto (2014)
Submitted by Paula Gautério (paulaporto_g@hotmail.com) on 2014-02-26T23:23:24Z No. of bitstreams: 1 Risk Assessment of Surface Water Contamination by Herbicide Residues Monitoring of Propanil Degradation.pdf: 93502 bytes, checksum: 38e9ac0033a248bd6aa69ef123f729d4 (MD5)